Gastric neuroendocrine neoplasias: manifestations and comparative outcomes. Issue 9 (September 2019) - Felder, S; Jann, H; Arsenic, R; Denecke, T; Prasad, V; Knappe-Drzikova, B; Maasberg, S; Wiedenmann, B; Pavel, M; Pascher, A; Pape, U F
Abstract : Although gastric neuroendocrine neoplasias (gNEN) are an orphan disease, their incidence is rising. The heterogeneous clinical course powers the ongoing discussion of the most appropriate classification system and management. Prognostic relevance of proposed classifications was retrospectively analysed in 142 patients from a single tertiary referral centre. Baseline, management and survival data were acquired for statistical analyses. The distribution according to the clinicopathological typification was gNEN-1 ( n = 86/60.6%), gNEN-2 ( n = 7/4.9%), gNEN-3 ( n = 24/16.9%) and gNEN-4 ( n = 25/17.6%), while hypergastrinemia-associated gNEN-1 and -2 were all low-grade tumours (NET-G1/2), formerly termed sporadic gNEN-3 could be subdivided into gNEN-3 with grade 1 or 2 and gNEN-4 with grade 3 (NEC-G3). During follow-up 36 patients died (25%). The mean overall survival (OS) of all gNEN was 14.2 years. The OS differed statistically significant across all subgroups with either classification system. According to UICC 2017 TNM classification, OS differed for early and advanced stages, while WHO grading indicated poorer prognosis for NEC-G3. Cox regression analysis confirmed the independent prognostic validity of either classification system for survival. Particularly careful analysis of the clinical course of gNEN-1 (ECLomas, gastric carcinoids) confirmed their mostly benign, but recurrent and extremely slowly progressive behaviour with low risk of metastasis (7%) and an efficient long-term control by repetitive endoscopic procedures. Our study provides evidence for the validity of current classifications focusing on typing, grading and staging. These are crucial tools for risk stratification, especially to differentiate gNEN-1 as well as sporadic gNET and gNEC (gNEN-3 vs -4).